2018
DOI: 10.3389/fmicb.2018.01788
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Crude Oil and Corexit 9500 in Arctic Seawater

Abstract: The need to understand the biodegradation of oil and chemical dispersants in Arctic marine environments is increasing alongside growth in oil exploration and transport in the region. We chemically quantified biodegradation and abiotic losses of crude oil and Corexit 9500, when present separately, in incubations of Arctic seawater and identified microorganisms potentially involved in biodegradation of these substrates based on shifts in bacterial community structure (16S rRNA genes) and abundance of biodegradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 84 publications
8
33
0
Order By: Relevance
“…All of these ingredients have previously been shown to serve as substrates for microbial growth (14)(15)(16). The stimulation of cell growth by Corexit 9500A is therefore not surprising, and similar findings have been reported elsewhere (17)(18)(19).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…All of these ingredients have previously been shown to serve as substrates for microbial growth (14)(15)(16). The stimulation of cell growth by Corexit 9500A is therefore not surprising, and similar findings have been reported elsewhere (17)(18)(19).…”
Section: Resultssupporting
confidence: 80%
“…S11 to S13 in the supplemental material). A dispersant-stimulated enrichment of potential hydrocarbon degraders, such as Colwellia and Rhodobacteraceae, has also been observed in other studies (14,18,25,32). This observation is not surprising, as Corexit 9500A contains a large hydrocarbon fraction in the form of alkane side chains of DOSS and petroleum distillates.…”
Section: Douglas Channel/hecate Strait Dilbit Degradationsupporting
confidence: 74%
“…These include (but are not limited to) bacterial taxonomic groups of Pseudomonadales (Leahy et al ., ; Seo et al ., ), Acidobacter (Seo et al ., ; Peng et al ., ), Gammaproteobacteria and Actinobacteria (Militon et al ., ; Peng et al ., ), Chloroflexi, Planctomycetes and Bacteroidetes (Peng et al ., ) (Table S2). Specific genera previously demonstrated to be associated with hydrocarbon‐impacted sites and high molecular weight polyaromatic hydrocarbons, such as bacterial OTUs identified as Anaerolineaceae, Caldilineaceae (Zhang et al ., ) and Lutibacter (McFarlin et al ., ) are shown to be elevated in abundance in samples from shallow and deep soils of A and B relative to section C (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have reported increased rates of petroleum biodegradation with the addition of chemical dispersants, including in the Arctic (2,3), using either enrichment cultures (4)(5)(6)(7) or indigenous microbial communities (1)(2)(3)(8)(9)(10)(11), the latter of which are more likely to better reflect rates observed for in situ conditions. Recently, some studies appear to demonstrate the opposite effect, with dispersant addition negatively affecting oil biodegradation in indigenous (12) and cultured (13) seawater through processes such as suppressing the growth of some oil degrading bacteria or competitive substrate biodegradation, reintroducing some debate regarding the influence of chemical dispersants on petroleum biodegradation.…”
Section: Introductionmentioning
confidence: 99%